The Impact of Green Human Resource Information on Organizational Growth Strategies - Abbas Fadhil Mohsin Al-Shammari; Habib Farhan Hamdan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Organizations today face increasing challenges related to environmental sustainability and social responsibility, requiring them to adopt modern management practices that enhance their sustainability and growth. This research aims to examine the concept of Green Human Resources Management (GHRM) and its role in supporting organizations' sustainable growth strategies. The research addresses the importance of adopting human resource management policies that take environmental dimensions into account, such as green recruitment and training, sustainable performance management, and rewards that promote positive environmental behaviors. It also explores the relationship between these dimensions and achieving sustainable organizational growth by improving operational efficiency, enhancing corporate image, and increasing employee and stakeholder satisfaction. The research relies on an analytical methodology that combines theoretical studies and practical experiences from organizations that have implemented green human resource strategies and achieved success in sustainable growth. The research concludes that integrating GHRM activities with organizational growth strategies leads to a sustainable competitive advantage and enhances organizations' ability to address modern environmental and economic challenges. What distinguishes our research from previous studies is its attempt to link the two disciplines of green human resource management and organizational growth strategy. This in itself is a rarity in this field compared to other research that links a single, precise discipline, given the importance of the role played by human resources and its impact on all business administration disciplines.